PENGARUH KUALITAS BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUKSI - Totok Sasongko; Moh Askiyanto; Yovita Yovita (Unitri Press, 2022)
The motivation behind this study was to decide the impact of the nature of unrefined components and creation processes on the nature of creation at PKS Darmex Agro Bengkayang West Kalimantan to some extent and all the while. This exploration is an examination utilizing quantitative strategies. Assurance of the example of this study utilizing basic irregular inspecting technique. The information assortment procedure utilized by the scientist is a survey. The information investigation strategy utilized is numerous direct relapse utilizing the SPSS variant 21 program. The consequences of the review demonstrate that to some extent the nature of unrefined substances fundamentally affects creation quality with a worth of t_count = 3.666 and the creation cycle essentially affects creation quality with a worth of t_count = 3.522. While, at the same time (together) the nature of unrefined components and creation processes essentially affect the nature of creation at PKS Darmex Agro Bengkayang West Kalimantan with an Fcount (21.690). What should be considered by organizations to further develop creation quality is to focus on unrefined components that should meet targets and live up to assumptions so the outcomes are fitting and offset with the items delivered. As well as improving support or upkeep, review and fix regularly on creation machines so as not to hamper the creation cycle.